LANDSCAPE APPROACH AND TYPOLOGY OF THE FORESTS OF THE STAVROPOL UPLAND - Anna Evgen’evna Kolesnichenko (Вестник Северо-Кавказского федерального университета)
The article deals with the history of the development of forest typology, typological classification of sci- entists, the classics of forestry. On the example of two of the forest massifs of the main types of forests in the Stavropol upland, and the relevant units of the landscape.